Pengembangan Bahan Ajar Berbasis PMRI Materi Perbandingan Senilai dan Berbalik Nilai Melalui Liveworksheets untuk Meningkatkan Kemampuan Literasi Numerasi dan SRL - Lintang Darmastuti; Lukman El Hakim; Flavia Aurelia Hidajat (Jurnal Pendidikan Indonesia, 2025)
The cognitive and affective abilities needed in this modern era are numeracy literacy and self-regulated learning (SRL). Based on the results of preliminary research conducted at a public junior high school in the Cijantung area on the material of comparison of value and reciprocal value, the three indicators of numeracy literacy were still below 50% and the average percentage of SRL success only reached 45.75%. Students' numeracy literacy and SRL abilities are influenced by the learning resources, media, and learning approaches used. Therefore, it is necessary to develop PMRI-based teaching materials through liveworksheets. The purpose of this study is to produce a product in the form of teaching materials using PMRI-based liveworksheets on the material of comparison of value and reciprocal value. This study was conducted in the even semester of the 2024/2025 academic year. The sample used consisted of 36 seventh grade students. The type of research used was R&D with the ADDIE model. Data analysis used the pre-test post-test control group method which was used to test the effectiveness of the product. The results of the study showed that the developed product was categorized as very valid (93,79%) based on expert assessments consisting of material aspects (89,93%), media (96,44%), and language (95,00%). The developed product was very practical (88,985) based on teacher responses (89,58%) and students (88,68%). Through n-gain calculations, this teaching material was effective in improving numeracy literacy skills to the high category (0,8) but could only improve SRL to the moderate level (0,46).